Elaboración de un proyecto de factibilidad para la implementación de una empresa procesadora y comercializadora de frutas exóticas en ceviche (mango y maracuyá), en el Cantón Catamayo, Provincia de Loja - MEDINA PINEDA, MARIA EUGENIA (2017)
The present project of research, has as purpose the "ELABORATION OF A PROJECT OF FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY PROCESSING AND MARKETER OF FRUITS EXOTIC IN CEVICHE (MANGO AND PASSION FRUIT), IN THE CANTON CATAMAYO, PROVINCE OF LOJA", objective that provides it opportunity of get to the consumer with a new product giving a value added. It was fundamental to methods used: deductive, inductive, descriptive - analytical and technical research as: observation, surveys and Bibliographical review; In addition was the market study, to establish the demand for the product, through the surveys applied to the families of the Catamayo canton, with a sample of 367 surveys and the supply of the product to all 31 companies. Getting results initial and partial that allowed forecasting the demands: potential the 79% (6,671); 76% (5.084) real and effective 75% (3.796). Taking into account that the average consumption per family per year is 34 units multiplied by the effective demand, future demand is 127.479 units. The offer to the year 37.111 units (18 companies); projected, with the growth rate of 3%, according to the database of the internal revenue service; with a demand unsatisfied of 90.368 units of ceviche for the first year. It is structured the plan of marketing: product, price, place, promotion and advertising. 6 Then be conducted the analysis of study technical where is took in consideration the capacity installed to the 100%, with a production of 121.545 units; Agreement, the number of productions and weekdays, the used capacity will have a share in the market of 28.860 units, this production compared with capacity installed, representing 33,33%; followed by the location of the plant and the engineering of the plans showing the processes, activities and times of the production process as also the distribution of the plant. Consecutively is study the organizational administrative and legal, where it is the trade name of the company "QUENITAMP" limited company, located in the neighborhood La Vega of the parish and Catamayo canton, formed by three partners, its useful life will be 5-year-old, also establishing the structural organization and its hierarchical levels of the company and the manual functions. Later the financial study determined the total investment of the project $22.541,86 which will be financed by capital partners 65% ($14.541,86) and a credit in the BanEcuador 35% ($8.000,00). According to the results, was conducted the financial evaluation, it determined the feasibility of the project, which analyzed the following indicators: net present value of $26.062,32,10; Period of recovery of Capital on 1 year, 9 months and 18 days; Internal rate of return of 49,43%; Relationship benefit cost of $1.31 for every dollar invested, the company obtained $0.31 cents of profit and sensitivity analysis, indicated that the project supports an increase in the costs of 14.38% with sensitivity of 0.99% and a decrease in revenue of 10,96%, with a sensitivity of 0.99%. Which, means that the project is feasible so it should run it. Finally the present thesis project, unveiled the conclusions and recommendations, bibliography, annexes and the index.